PENGARUH SISTEM PEMBELAJARAN SHIFT TERHADAP MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA KATOLIK DI SEKOLAH DASAR NEGERI AMOL - Mones, Anselmus Yata; Kolo, Fransiskus Silamus (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2022)
The problem in this study is the spread of the Covid-19 Pandemic that occurred in various regions in East Nusa Tenggara Province. This has an impact on education, especially in the learning process that changes from face-to-face learning to a shift learning system. The problem examined in this study is whether there is an effect of the shift learning system on the learning motivation of students in Class V and VI of Amol State Elementary School. The purpose of this study was to describe the effect of the shift learning system on students' learning motivation in the subjects of Catholic Religious Education Class V and VI at SD Negeri Amol. The type of method used in this research is quantitative research with a correlation approach. The research location is in SD Negeri Amol. Informants in this study were students of Class V and VI. Data collection techniques used are observation and questionnaires. While the data analysis techniques include correlation analysis techniques and simple regression techniques. Based on calculations using the correlation formula, it was found that the correlation between the shift learning system and the learning motivation of students was 0.1283%, which was relatively low. Meanwhile, using a simple regression formula of 0.081 (low). The results showed that there was an effect of shift learning on the learning motivation of Class V and VI students, meaning that the lower or less the value of shift learning, the lower the level of learning motivation of students, and vice versa if the higher the value of shift learning, the higher the level of learning motivation of students.